1991
DOI: 10.2166/wst.1991.0422
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Beach Water Pollution and Health-Related Bathing Water Standards in Hong Kong

Abstract: A prospective epidemiological study was undertaken in Hong Kong in 1987, in which 18,741 usable responses were obtained. It showed bathing in the coastal beaches of Hong Kong poses an increased risk of developing gastrointestinal, ear, eye, skin, respiratory and total illness. Swimmers immersed in the more polluted beach waters are exposed to a significantly higher risk of contracting swimming-associated gastrointestinal, skin, respiratory and total illness. E. coli was found to be the best indicator for swimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Regardless of the application, it is clear that the most important characteristic of any indicator or indicator system is its ability to indicate possible health risk. This can be shown directly, through conducting epidemiological studies, in which the association between water quality indicators and health outcomes are assessed ( Cabelli et al, 1979 ; Cheung et al, 1990 ; Colford et al, 2002 ; Hellard et al, 2001 ; Payment et al, 1991 , 1997 ; Seyfried et al, 1985a , 1985b ; Zmirou et al, 1987 ). An indirect means of demonstrating correlation between indicators and health risk would be the assessment of pathogen levels and levels of prospective indicators ( Gerba et al, 1979 ; Havelaar, 1993 ; Havelaar et al, 2003 ; Labelle et al, 1980 ; Leclerc et al, 2000 ; Robertson, 1984 ; Seyfried et al, 1984 ).…”
Section: Characteristics Of Indicatorsmentioning
confidence: 99%
“…Regardless of the application, it is clear that the most important characteristic of any indicator or indicator system is its ability to indicate possible health risk. This can be shown directly, through conducting epidemiological studies, in which the association between water quality indicators and health outcomes are assessed ( Cabelli et al, 1979 ; Cheung et al, 1990 ; Colford et al, 2002 ; Hellard et al, 2001 ; Payment et al, 1991 , 1997 ; Seyfried et al, 1985a , 1985b ; Zmirou et al, 1987 ). An indirect means of demonstrating correlation between indicators and health risk would be the assessment of pathogen levels and levels of prospective indicators ( Gerba et al, 1979 ; Havelaar, 1993 ; Havelaar et al, 2003 ; Labelle et al, 1980 ; Leclerc et al, 2000 ; Robertson, 1984 ; Seyfried et al, 1984 ).…”
Section: Characteristics Of Indicatorsmentioning
confidence: 99%
“…Valores de referencia: CT =1000 UFC/100 ml, valor permisible del Decreto 1594 de 1984 E. coli = 269 UFC/100 ml , (Cheung, 1989: tasa de incidencia de 6.5 casos por mil de gastroenteritis aguda) Enterococos = 232 UFC/100 ml, (Bandaranayake, 1995: t tasa de incidencia de 22 casos por mil de gastroenteritis aguda) Promedios geométricos obtenidos para las playas…”
Section: Análisis Descriptivounclassified
“…Gobiernos trabajan de la mano con estos grupos, para calificar sus destinos turísticos y garantizar así una afluencia de visitantes que buscan calidad en los servicios y en el agua de contacto primario. Estudios realizados por diversas agrupaciones e investigadores hacen asociaciones entre los niveles de contaminación de las aguas de recreo y la aparición de enfermedades (CABELLI, 1983;CHEUNG, 1989, CEPIS, 2000EPA, 1999;EL SHARKAWI, 1979;FLEISHER, 1996;FERNANDEZ, 1992;FEWTRELL, 1993;HENDERSON, 1968;LIGHTFOOT, 1989;PHLS, 1959;OMS, 1998OMS, /2003 CSHP; Blue Flag y Tidy Britain Group, entre otros).…”
Section: Introductionunclassified
“…A number of studies have also suggested that bathing in poor quality marine waters implies an increased risk of developing illnesses other than gastroenteritis (Cheung et al, 1991;Corbett et al, 1993;Fleisher et al, 1996;Fleisher et al, 1998). Fleisher et al (1996) estimated signi®cant doseresponse functions for ear ailments and for acute febrile respiratory illnesses in the UK, while Fleisher et al (1998) found that bathers at beaches contaminated with domestic sewage were also at increased risk of ear and eye infections.…”
Section: Epidemiological Modelsmentioning
confidence: 99%